Conceptual Metaphors as Expressions of Humanism in Laki-Laki di Taman Senja - Rizky Anugrah Putra (Applied Linguistics: Innovative Approaches and Emerging Trends, 2025)
This study explores the intersection of cognitive linguistics and literature to evaluate the humanistic values embedded within metaphors in the short story Laki-laki di Taman Senja by Muhamad Abi Fadila. Utilizing a qualitative content analysis combined with a stylistic approach, the research systematically classified textual excerpts against established cognitive metaphorical source domains. The analysis identified four primary conceptual categories manipulated by the author which are the human body, animals and plants, light and darkness, and direction and movement. Rather than functioning purely as aesthetic stylistic embellishments, these four distinct linguistic structures operate as essential cognitive frameworks. They map the protagonist's complex emotional landscapes, directly articulating three major humanistic theme which are the profound existential struggle against modern urban monotony, the transformative power of non-judgmental empathy, and the fundamental necessity of self-acceptance. Ultimately, these metaphorical mappings successfully bridge internal psychological realities with external social dynamics, offering profound insights into the human condition and individual resilience amidst contemporary societal alienation.